Patterns and correlates of the co-use of marijuana with any tobacco and individual tobacco products in young adults from Wave 2 of the PATH Study. (May 2019) - Cohn, Amy M.; Abudayyeh, Haneen; Perreras, Lexie; Peters, Erica N.
Abstract: Background: Past-month marijuana use has increased significantly among US young adults (aged 18–24) and marijuana use often overlaps with tobacco use. This study investigated the relative prevalence and correlates of individual tobacco product use among young adult marijuana and tobacco users to determine if unique typologies could be identified. Method: Data were from young adults (18–24) in Wave 2 of the Population Assessment of Tobacco and Health (PATH) Study. Analyses examined the prevalence of different patterns of past 30-day marijuana and tobacco use and co-use. Weighted adjusted models were used to examine correlates of different marijuana and individual tobacco co-use profiles (compared to no-use of either product). Results: Prevalence estimates showed that 30.9% of young adults report past month tobacco-only use, 21.3% report past-month co-use of marijuana and at least one tobacco product, and 4.5% report past 30-day marijuana-only use. Correlates of co-use differed by tobacco product. Using 3+ tobacco products and frequency of past 30-day alcohol use were robustly and consistently associated with each marijuana and individual tobacco co-use profile and any co-use of marijuana with tobacco. Conclusions: Among US young adults between 2014 and 2015, co-use of marijuana and tobacco was common, and there was heterogeneity in correlates associated with use of different tobacco products among those who used marijuana. Different correlates suggest different targets for marijuana and tobacco prevention and intervention in this age group. Highlights: 20% of young adults report marijuana and tobacco co-use. Correlates of co-use differed by tobacco product of use. Alcohol use and number of products were robust correlates of co-use.